1988
DOI: 10.1159/000238578
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Pharmacokinetics of Ceftriaxone in Patients with End-Stage Renal Disease and Hemodialysis

Abstract: We report the pharmacokinetic parameters of ceftriaxone in 11 patients on hemodialysis with end-stage renal disease (ESRD; creatinine clearance < 5 ml/ min/1.73 m2). The patients were studied during the interdialysis period and during 4h of hemodialysis. The mean age was 53.4 years. After the administration of 1 g of ceftriazone during a constant intravenous infusion over a 30-min period, t½ was 16.6 h, β was 0.0418 ± 0.0106 h-1, VD was 14.5 ± 3.0 liters/1.73 m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…However, a recent study reported a 41 % reduction in serum concentration (68 to 40 mg/L) and average tlh (16.6 to 4.88h) with 4-hour haemodialysis in II patients with end-stage renal disease (Garcia et al 1988). At 28 hours after a dose of ceftriaxone Ig including a 4-hour haemodialysis, plasma concentrations were still within the therapeutic range (40 mg/L).…”
Section: Renal Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…However, a recent study reported a 41 % reduction in serum concentration (68 to 40 mg/L) and average tlh (16.6 to 4.88h) with 4-hour haemodialysis in II patients with end-stage renal disease (Garcia et al 1988). At 28 hours after a dose of ceftriaxone Ig including a 4-hour haemodialysis, plasma concentrations were still within the therapeutic range (40 mg/L).…”
Section: Renal Diseasementioning
confidence: 97%
“…Anephric patients with normal extrarenal clearance showed a moderate increase in tlh (14.4 to 17h) with greater V d (Garcia et al 1988;Wise et al 1985). Anephric patients with concurrent decrease in extrarenal clearance (> 80%), however, showed a significant prolongation of tlh (> 50h), requiring dose adjustment (Stoeckel et al 1984b).…”
Section: Renal Diseasementioning
confidence: 99%
“…While its elimination half-life (T1/2) is 6–9 h in normal subjects, it prolongs to 16.6 h in patients with ESRD: creatinine clearance (CCr) ˂5 mL/min/1.73 m 2 [2]. Although CTX is dialyzable, its blood concentration achieves the bacteriocidal range during hemodialysis independent of CCr [2].…”
Section: Discussionmentioning
confidence: 99%
“…While its elimination half-life (T1/2) is 6–9 h in normal subjects, it prolongs to 16.6 h in patients with ESRD: creatinine clearance (CCr) ˂5 mL/min/1.73 m 2 [2]. Although CTX is dialyzable, its blood concentration achieves the bacteriocidal range during hemodialysis independent of CCr [2]. As it has a moderately longer T1/2 and is not affected by hemodialysis, the administration of a once-daily dose of CTX is rational and practical to eradicate susceptible organisms in patients with severely impaired renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: HD = haemodialysis; PD = peritoneal dialysis; CAPD = continuous ambulatory peritoneal dialysis; NC = no change; qxh = every x hours. tion (14.4 to 17h) due to significant nonrenal elimination which may be facilitated by the increased free fraction often present in these patients (Garcia et al 1988;Wise & Wright 1985). Dosage adjustment in renal failure is not indicated for cefoperazone.…”
Section: Renal Impairmentmentioning
confidence: 99%